Preparation of NiS/ZnIn2S4 as a superior photocatalyst for hydrogen evolution under visible light irradiation - Wei, Liang; Chen, Yongjuan; Zhao, Jialin; Li, Zhaohui (Beilstein Journal of Nanotechnology, 2013)
In this study, NiS/ZnIn2S4 nanocomposites were successfully prepared via a facile two-step hydrothermal process. The as-prepared samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). Their photocatalytic performance for hydrogen evolution under visible light irradiation was also investigated. It was found that the photocatalytic hydrogen evolution activity over hexagonal ZnIn2S4 can be significantly increased by loading NiS as a co-catalyst. The formation of a good junction between ZnIn2S4 and NiS via the two step hydrothermal processes is beneficial for the directional migration of the photo-excited electrons from ZnIn2S4 to NiS. The highest photocatalytic hydrogen evolution rate (104.7 μmol/h), which is even higher than that over Pt/ZnIn2S4 nanocomposite (77.8 μmol/h), was observed over an optimum NiS loading amount of 0.5 wt %. This work demonstrates a high potential of the developing of environmental friendly, cheap noble-metal-free co-catalyst for semiconductor-based photocatalytic hydrogen evolution.
Keywords: co-catalyst; hydrogen evolution; NiS; photocatalytic; photocatalysis; visible light